INDIA’S SOFT POWER DIPLOMACY: LEVERAGING CULTURE, DIASPORA, AND YOGA FOR GLOBAL INFLUENCE - Verma, Durgesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The cultural past, large diaspora, and global yoga popularity has made India’s soft power diplomacy ever more crucial in its search of world influence. India’s cultural diplomacy is playing a pivotal role in interconnected world where the expression of a nation’s identity may eclipse traditional hard power dynamics. Particularly by focusing on initiatives such as the ICCR and international cultural events; this study explores how India effectively uses its artistic, musical, and cinematic resources to raise its global presence. One of the largest diasporas globally, which serves as an unofficial ambassador for India helps to enhance India’s prominence both politically and economically. Initiatives undertaken by the government, like Pravasi Bharatiya Divas and various diaspora involvement, have strengthened these relations centralising the diaspora in India’s soft power strategy. Yoga, rooted deeply in India’s spiritual and intellectual traditions, has gone global and enhances India’s reputation as a nation of peace, wellness, and spirituality. The International Day of Yoga, approved by the UN in 2015, has been rather successful underscoring India’s leadership in health and wellness diplomacy. India’s soft power diplomacy has to negotiate geopolitics, internal socio-political issues, and competition from other developing countries. Notwithstanding these obstacles, public diplomacy, online platforms, and higher education give India’s soft power opportunity for rather significant development. India is becoming more and more relevant worldwide by making appropriate use of its diaspora and cultural treasures. This paper highlights the significant potential of India’s soft power diplomacy to influence its overseas relations, thereby enhancing its leadership in the twenty-first century, through the use of culture, diaspora, and yoga.